Educação ambiental e ensino contextualizado de matemática no semiárido: um estudo de caso no Município de São João do Cariri - PB - Lacerda, Pryscilla Barbosa de (2018)
The present study aimed to investigate the pedagogical practice of teachers within Environmental Education (EA) placed in context in the Semiarid. This qualitative case-study research involved, as central questions, two Mathematics teachers’ conceptions regarding the environment where they live; the contextualization process, and how they implement the contextualized learning in classroom. The study was conducted after data collected through semi-structured interviews and after analyzing documents prepared by the teachers, who teach in two public schools in the municipality of São João do Cariri, PB. Using the interviews, we identified that teachers have a vast knowledge on the environment where they live and that they carry with them two conceptions concerning the meaning of contextualizing, they are: to associate the contents of Mathematics with everyday aspects and to relate Mathematics with other areas of knowledge. The teachers also pointed out the purposes and contributions of contextualization in students’ education and in the development of teaching-learning processes more committed to the reality experienced in the semi-arid region of Paraiba. By analyzing the documents, we verified how the contextualized approach materializes in the teachers' classes, identifying the development of projects as a viable alternative. The results of this study reveal that the two Mathematics teachers recognize the importance of contextualization and therefore, they are engaged in the implementation of a practice consistent with their conceptions. Thus, we believe that the reflections developed in this research help to highlight the importance of EA contextualized in the semi-arid perspective, being able to direct new pedagogical practices committed to the critical and reflexive education of the subjects that coexist in the region.